Jim Thorpe : original All-American - Bruchac, Joseph, 1942- (Speak, 2008)
A fictionalized biographical novel in which Native American athlete and Olympic gold medalist Jim Thorpe discusses his life, focusing on the years he spent at Pennsylvania's Carlisle School where his abilities were first noticed by his coach, Pop Warner.